2020
DOI: 10.21203/rs.3.rs-19280/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the Gut Microbiota Disturbance in Rat Models of Irritable Bowel Syndrome Induced by Maternal Separation and Multiple Early-life Adversity

Abstract: Background: The aims of this study was to identify the effect of modeling procedures on bacterial communities and investigate whether different modeling procedures lead to consistent patterns of gut microbiota compositions. Methods: Two IBS rat models (MS alone and multiple-early-adversity modeling) were established and the gut microbiotas were analyzed using 16S-rRNA-based high-throughput sequencing methods. Results: Rats from both models exhibited visceral hypersensitivity and the two model groups exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several recent studies have reported significant differences in β-diversity at the phylum level [21,42,51,52,62,64,68,92,94,95]. However, one study reported a significant difference at the genus level in stressed animals versus controls and a separate study reported significant differences at both the phylum and genus levels [83,101]. Seven studies reported no significant differences to β-diversity.…”
Section: Gut Microbial Diversitymentioning
confidence: 97%
“…Several recent studies have reported significant differences in β-diversity at the phylum level [21,42,51,52,62,64,68,92,94,95]. However, one study reported a significant difference at the genus level in stressed animals versus controls and a separate study reported significant differences at both the phylum and genus levels [83,101]. Seven studies reported no significant differences to β-diversity.…”
Section: Gut Microbial Diversitymentioning
confidence: 97%
“…Furthermore, evidence is emerging that increases in the abundance of Cyanobacteria in gut communities is correlated with gastrointestinal and neurodegenerative disease [ 41 ]. For example, increased abundances of Vampirovibrio , specifically, have been found in colorectal fecal communities in a rat model of irritable bowel syndrome established by subjecting rats to multiple forms of stress, including early maternal separation [ 42 ]. Additionally, it is worth noting that, the one other study to compare the gut communities of paired and isolated prairie voles, found increases in the abundance of a Gastranaerophilales gut metagenome species in isolated animals [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the notable taxa that differed between paired and isolated voles, Anaerostipes and Lactobacillaceae , which had a greater abundance in the fecal communities of paired voles, have previously been associated with putative benefits to host health either through the production of short chain fatty acids (SCFAs) [ 43 , 44 , 45 ] or regulation of pathogen growth and colonization [ 23 , 46 ]. Conversely, several taxa, such as Enterococcus , Metaprevotella , and Staphylococcaceae that had a greater abundance in the fecal communities of isolated voles have previously been associated with disease [ 35 , 42 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%